Heterozygous variants in PRPF8 are associated with neurodevelopmental disorders. Issue 9 (11th May 2022) - O'Grady, Lauren; Schrier Vergano, Samantha A.; Hoffman, Trevor L.; Sarco, Dean; Cherny, Sara; Bryant, Emily; Schultz‐Rogers, Laura; Chung, Wendy K.; Sacharow, Stephanie; Immken, Ladonna L.; Holder, Susan; Blackwell, Rebecca R.; et al.
Abstract: The pre‐mRNA‐processing factor 8, encoded by PRPF8, is a scaffolding component of a spliceosome complex involved in the removal of introns from mRNA precursors. Previously, heterozygous pathogenic variants in PRPF8 have been associated with autosomal dominant retinitis pigmentosa. More recently, PRPF8 was suggested as a candidate gene for autism spectrum disorder due to the enrichment of sequence variants in this gene in individuals with neurodevelopmental disorders. We report 14 individuals with various forms of neurodevelopmental conditions, found to have heterozygous, predominantly de novo, missense, and loss‐of‐function variants in PRPF8 . These individuals have clinical features that may represent a new neurodevelopmental syndrome.